2018
DOI: 10.1177/1071100718774005
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation Rate Differences Between Open Reduction Internal Fixation and Primary Arthrodesis of Lisfranc Injuries

Abstract: Level III, retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 37 publications
1
11
0
1
Order By: Relevance
“…5557 Table 4 summarises the comparative studies of ORIF versus primary arthrodesis in lesions of the Lisfranc joint. 16,19,20,58,60…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5557 Table 4 summarises the comparative studies of ORIF versus primary arthrodesis in lesions of the Lisfranc joint. 16,19,20,58,60…”
Section: Resultsmentioning
confidence: 99%
“…However, Buda et al in a recent article concluded that if we exclude hardware removal, patients with Lisfranc lesions treated with ORIF do not have a higher rate of re-operation (29.5%) compared with those who are treated with a primary partial arthrodesis (29.6%). 20 The most common causes of re-operation are post-traumatic OA in patients treated with ORIF and non-union in those treated with primary arthrodesis.…”
Section: Controversiesmentioning
confidence: 99%
“…Crush-Verletzungen, wie sie im Rahmen von Hochrasanztraumen vorkommen, sind prognostisch am ungünstigsten [10,11,26]. schen Auswertung heraus, ergeben sich keine Differenzen in der Reoperationsrate [42]. Eine Cochrane-Metaanalyse musste ohne wegweisende Erkenntnisse hinsichtlich des optimalen Therapiealgorithmus für Lisfranc-Luxationen eingestellt werden [43,44].…”
Section: Ergebnisseunclassified
“…These are uncommon injuries, with an estimated incidence of 39.2/100000/year 1 . Despite this, numerous techniques exist for their fixation, including the use of plate fixation, fixation with Kirschner wires and fixation with screws 2–8 . Internal fixation using plating may be performed using pre‐contoured dedicated foot plates, which are designed specifically for the anatomy of the foot.…”
Section: Introductionmentioning
confidence: 99%